Gender mainstreaming in water reuse: guidelines for planners, investors, project designers and operators - International Water Management Institute (International Water Management Institute, 2023)
Gender equity is essential for the success of water reuse projects in the Middle East and North Africa (MENA), yet women remain underrepresented in decision-making, employment, and planning processes. This IWMI brief promotes gender mainstreaming as a practical entry point toward a more transformative approach one that challenges systemic inequalities and redistributes power and resources. Women, especially in countries like Egypt where they represent a significant share of the agricultural labor force, are often excluded from water reuse governance and technical training, despite their key roles. The brief outlines a project cycle-based framework with guiding questions to integrate gender at every stage, from initiation to evaluation. Real-life cases, such as those in Kafr El-Sheikh, reveal how lack of safety assurances and market stigma force marginalized women to sell low-demand crops irrigated with drainage water outside their communities. Removing institutional barriers to female employment and ensuring access to information and resources can create more inclusive and effective outcomes. By embedding gender perspectives into employment strategies, service design, and policy dialogues, IWMI advocates for water reuse systems that reflect the needs, voices, and capacities of all stakeholders.